1986
DOI: 10.1159/000124458
|View full text |Cite
|
Sign up to set email alerts
|

Two Possible Mechanisms for Precocious Puberty Induced in Female Rats by Pituitary Grafts

Abstract: Many reports indicate that prolactin has a role in puberty occurrence. The present study was developed to evaluate the action of pituitary grafts on puberty. Female rats grafted on day 21 with ‘adult’ (90 days old) or ‘young’ (21 days old) pituitaries showed precocious vaginal opening and first estrus. The puberty advancement induced by ‘adult’ transplants was due to an increase in plasma prolactin values and can be blocked by bromocriptine treatment. The puberty advancement induced by ‘young’ transplants was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

1988
1988
2000
2000

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
2
5
0
Order By: Relevance
“…These results confirm our initial hypothesis [4,10] concerning the existence of two mechanisms in precocious puberty induced by pituitary grafts: a PRL-dependent one when 'adult' pituitaries were used, and another LH-dependent one when 'young' pituitaries were used. This mechanism would be similar to the well-known precocious puberty induced by injections of HCG and PHSG.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…These results confirm our initial hypothesis [4,10] concerning the existence of two mechanisms in precocious puberty induced by pituitary grafts: a PRL-dependent one when 'adult' pituitaries were used, and another LH-dependent one when 'young' pituitaries were used. This mechanism would be similar to the well-known precocious puberty induced by injections of HCG and PHSG.…”
Section: Discussionsupporting
confidence: 87%
“…Previous results [4,10] suggested that the precocious pu berty induced by a 'young' graft was not mediated by an in crease in PRL secretion, since no increased PRL plasma levels were obtained and the effect of the pituitary graft was not blocked by bromocriptine.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, the advancement induced by grafting a pituitary gland from a 'young' donor (21 days old) was not associated with increased prolactin concentrations and cannot be blocked by bromocriptine. These results suggested the existence of two possible mechanisms in precocious puberty induced by pituitary gland grafts: one being prolactin-dependent and the other not directly related to prolactin (Gonzalez et al, 1986).…”
Section: Introductionmentioning
confidence: 82%
“…Blood samples were obtained before daily injections of bromocriptine or vehicle at 10:00 h on Days 21, 25, 35 and at decapitation performed on the day of balano-preputial separation. Samples were obtained by jugular venepuncture after light ether anaesthesia as described previously (Gonzalez et al, 1986).…”
Section: Methodsmentioning
confidence: 99%